Comparative efficacy of amphotericin B-loaded chitosan nanoparticles and free amphotericin B drug against Leishmania tropica - Aamir Sohail (SpringerOpen, 2021)
Abstract Background The preparation of an effective drug delivery formulation is an urgent need to treat cutaneous leishmaniasis (CL). Pentavalent antimonials and Amphotericin B (AmB) are considered to treat leishmaniasis; however, their clinical usage is hampered by poor solubility, high cost, toxicity, and the emergence of drug-resistant Leishmania spp. The drug delivery systems (DDS) could be used as an alternative treatment option for the treatment of CL to circumvent these problems. We tested the antileishmanial efficacies of free AmB and amphotericin B-loaded chitosan nanoparticles (AmB-CNPs) under in vitro conditions. Results Chitosan nanoparticles (CNPs) were synthesized using the ionic gelation method with negatively charged tripolyphosphate (TPP). During the synthesis of CNPs, AmB was incorporated into the nanoparticles (NPs). The NPs were characterized for their size, surface morphology, encapsulation efficacy (EE), drug loading content (DLC), and surface charge using different techniques. Their efficacy was evaluated against promastigotes and axenic amastigotes forms of Leishmania tropica using MTT assay. The synthesized AmB-CNPs displayed a spherical shape with a mean particle size of 118 nm, a positive zeta potential of (+ 6.21 ± 2.02 mV), and an encapsulation efficacy of 88%. Dynamic light scattering technique (DLS) shows that the average size of prepared AmB-CNPs was 95.5 nm. Free AmB presented very low efficacy (only 65% and 67% inhibition of the promastigotes and axenic amastigotes parasite load), whereas AmB-CNPs exhibited 90% and 84% parasite inhibition after 72 h incubation. The AmB-CNPs exhibited significantly higher efficacy than free AmB in terms of reduction in parasite viability. Half-maximal inhibitory concentration (IC50) measured values of the AmB-CNPs were significant lowers than free AmB. Conclusions The present data indicated that AmB-CNPs exhibited vigorous anti-leishmanial activity than free AmB by dose and time-dependent manner. This formulation can be used for local therapy of CL after in vivo efficacy conformational studies.